Evaluating the multi-dimensional values of bridge-tourism integration: an empirical study using the DEMATEL—ISM—MICMAC method - Yan Du; Han He (Frontiers in Public Health, 2025)
In the context of high-quality tourism development and the increasing emphasis on ecological conservation, bridge-tourism integration has emerged as an innovative model combining cultural, ecological, and economic values, demonstrating significant research potential. However, systematic analysis and comprehensive evaluation of this integration remain limited. To address this gap, the present study applies the integrated Decision-Making Trial and Evaluation Laboratory, Interpretive Structural Modeling, and Cross-Impact Matrix Multiplication Applied to Classification (DEMATEL—ISM—MICMAC) approach to construct a multi-layered evaluation model for assessing these values. The findings identify historical context and architectural design as key drivers, significantly enhancing cultural appeal and ecological value. Intermediate factors, such as cultural activities and geographical location, are essential links within the system. Sub-base factors, including policy regulations and environmental friendliness, provide critical support for cultural preservation and ecological sustainability. In contrast, base-level factors, such as economic benefits and visitor satisfaction, directly reflect the integrated performance of bridge-tourism development. The study concludes that, through systematic management and policy support, bridge-tourism integration can effectively balance cultural preservation, ecological protection, and economic development, laying a solid foundation for its sustainable advancement.